Media Practices and Forced Migration: Trust Online and Offline - Graf, Heike (2018)
This article explores the relationship between online and offline practices in the special case of forced migration. By applying a central category in social relations, trust/distrust as developed by Niklas Luhmann, this article contributes to the understanding of forced migration in the digital age. It presupposes that, without a strategy of trust, it would be almost impossible to cope with situations of unfamiliarity and uncertainty. By interviewing refugees, the question is in what contexts the refugee recognizes that they can trust (or not). The article concludes that through the combination of on- and offline communication practices, more varied mechanisms for the creation and stabilization of trust are provided. In contexts of unfamiliarity, interpersonal relations with the native inhabitants play an important role in bridging online and offline worlds.